Lepus Linnaeus 1758 - Robert S. Hoffmann (Smithsonian Institution Press, 1993)
Lepus Linnaeus, 1758. Syst. Nat., 10th ed., 1:57. TYPE SPECIES: Lepus timidus Linnaeus, 1758. SYNONYMS: Allolagus Ognev, 1929; Boreolagus; Barrett-Hamilton, 1911; Chionobates Kaup, 1829; Eulagos Gray, 1867; Eulepus Acloque, 1899; Indolagus Gureev, 1953; Lagos Palmer, 1904; Macrotolagus, Mearns, 1895; Poecilolagus Lyon, 1904; Proeulagus Gureev, 1964 Tarimolagus Gureev, 1947. COMMENTS: Formerly included Bunolagus; see Petter (1972b); and originally all other genera except Pentalagus. The taxonomy of this genus remains controversial. L. crawshayi (including whytei), peguensis, ruficaudatus, and siamensis have been variously treated as separate species or have been included in nigricollis. L. europaeus, corsicanus, granatensis, tolai, and tibetanus have been placed in capensis or treated as distinct species; see comments therein. Published as part of Robert S. Hoffmann, 1993, Order Lagomorpha, pp. 807-827 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 814, DOI: 10.5281/zenodo.7353088